2020
DOI: 10.3389/fpsyg.2020.567505
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety Severity, Perceived Risk of COVID-19 and Individual Functioning in Emerging Adults Facing the Pandemic

Abstract: The COVID-19 pandemic is showing a strong impact on people in terms of uncertainty and instability it has caused in different areas of daily life. Uncertainty and instability are also emotions that characterize emerging adulthood (EA). They generate worries about the present and the future and are a source of anxiety that impacts negatively on personal and interpersonal functioning. Anxiety seems a central effect of the pandemic and recent studies have suggested that it is linked to COVID-19 risk perception. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
36
1
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 77 publications
5
36
1
10
Order By: Relevance
“…In these regions, individuals who violate norms are seen as adhering to the cultural ideal of individualism for autonomy, which may enhance their status in society ( Kinias et al, 2014 ) and is less likely to cause moral outrage from others ( Stamkou et al, 2019 ). On the other hand, in regions where individualistic culture prevails, individuals are less aware of the connection between themselves and the collective, which is associated with a lower perceived risk of infectious diseases ( Germani et al, 2020 ). Accordingly, we observed that American participants but not Chinese participants in the high interpersonal trust group were less aware of the infection risk caused by others, and the positive effect of interpersonal trust on reducing unnecessary outdoor activities was affected by the decline in the perception of infection risk.…”
Section: Discussionmentioning
confidence: 99%
“…In these regions, individuals who violate norms are seen as adhering to the cultural ideal of individualism for autonomy, which may enhance their status in society ( Kinias et al, 2014 ) and is less likely to cause moral outrage from others ( Stamkou et al, 2019 ). On the other hand, in regions where individualistic culture prevails, individuals are less aware of the connection between themselves and the collective, which is associated with a lower perceived risk of infectious diseases ( Germani et al, 2020 ). Accordingly, we observed that American participants but not Chinese participants in the high interpersonal trust group were less aware of the infection risk caused by others, and the positive effect of interpersonal trust on reducing unnecessary outdoor activities was affected by the decline in the perception of infection risk.…”
Section: Discussionmentioning
confidence: 99%
“…During pandemic, emerging adults resulted to be extremely vulnerable to psychological distress and addictive behaviors (Germani et al, 2020; McPhee et al, 2021; Simone et al, 2021). Emerging adulthood is characterized by instability on different life domains, as youths are still exploring their adult identities (Arnett, 2000), but this instability was exacerbated by health-emergency, prompting psychological distress (Bartel et al, 2020; Germani et al, 2020; McPhee et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…During pandemic, emerging adults resulted to be extremely vulnerable to psychological distress and addictive behaviors (Germani et al, 2020; McPhee et al, 2021; Simone et al, 2021). Emerging adulthood is characterized by instability on different life domains, as youths are still exploring their adult identities (Arnett, 2000), but this instability was exacerbated by health-emergency, prompting psychological distress (Bartel et al, 2020; Germani et al, 2020; McPhee et al, 2021). As regards the Italian context, pre-pandemic conditions of emerging adults were characterized by a widespread unemployment, so that most youths continued to live with their parents, or moved to large cities to find job, with consequent housing emergency (Crocetti et al, 2015; European Communities, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Una posible explicación es que los AE se encuentran en una fase del desarrollo en el que perciben una mayor incertidumbre y ansiedad por el futuro, sería interesante valorar si esta población ya presentaba niveles más elevados de ansiedad y depresión previos a la pandemia. (Germani et al, 2020).…”
Section: Discussionunclassified